2018
DOI: 10.9734/ejnfs/2018/42883
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Nutritional Anaemia among Adolescent Girls of Distt. U.S. Nagar, Uttarakhand

Abstract: Aim: Present study was carried out to determine the prevalence and epidemiological correlates of anaemia among adolescent girls (AGs) of district U. S. Nagar, Uttarakhand (India). Methodology: A cross sectional study was conducted between March-November 2017 among 880 AGs (10-19 years) in 88 anganwadi (AWC) centers covering three blocks one each from rural, urban and tribal blocks of district U.S. Nagar. A pre-structured questionnaire was used to collect socio-demographic, dietary and menstrual health data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Anemia in the third trimester of pregnancy is associated with adverse maternal and neonatal outcomes. A retrospective study from Pakistan reported both adverse maternal and neonatal outcomes such as postpartum hemorrhage, prolonged or obstructed labor, gestational hypertension, and preeclampsia, with neonatal complications ranging from early neonatal death, stillbirth, preterm delivery, to low birth weight [2]. Moreover, anemia risk in urban women is reduced up to 73% due to better health and sanitation facilities [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia in the third trimester of pregnancy is associated with adverse maternal and neonatal outcomes. A retrospective study from Pakistan reported both adverse maternal and neonatal outcomes such as postpartum hemorrhage, prolonged or obstructed labor, gestational hypertension, and preeclampsia, with neonatal complications ranging from early neonatal death, stillbirth, preterm delivery, to low birth weight [2]. Moreover, anemia risk in urban women is reduced up to 73% due to better health and sanitation facilities [3].…”
Section: Discussionmentioning
confidence: 99%
“…Iron, as part of structural component of hemoglobin, plays an important role in the transportation of oxygen from the lungs to the body cells [1]. Iron is essential to produce hemoglobin by erythroblasts; thus, if there is an insufficient supply of iron, the cells fail to produce hemoglobin, resulting in a condition known as "anemia" [2]. The normal level of hemoglobin for non-pregnant women and males (aged 15 years and above) is 120 gm/L and 130 gm/L respectively, according to the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have established that anemia is significantly more prevalent in individuals who consume their main meal only once per day compared to those who have it three times per day. However, it is also noted that anemia is more common among those who eat two meals per day (44)(45)(46). A majority of studies involving women have found a correlation between meal frequency and the incidence of anemia (45,47,48).…”
Section: Nutritional Factors Meal Frequencymentioning
confidence: 99%
“…Research suggests that most nursing students are young adults, typically aged between 19 and 21, and often come from lower middle-class backgrounds (7). It has been observed that students frequently skip meals, a concerning trend (7,11,12), and this behavior may be influenced by factors like low household income, even when students are not necessarily lacking appetite (13). In Pakistan, nurses constitute a significant portion of the healthcare workforce.…”
Section: Introductionmentioning
confidence: 99%